A design of ecological restoration and eco-revetment construction for the riparian zone of Xianghe Segment of China's Grand Canal. Issue 4 (3rd July 2016) - Tian, Ye; Guo, Ziqi; Zhong, Wei; Qiao, Yanchao; Qin, Jingxin
ABSTRACT: The riparian zone is a unique landscape component that represents an ecological transition between aquatic and terrestrial ecosystems. The restoration of riparian zones has become an ecological focus in the realms of both urban development planning and watershed management. This paper applies the concept of landsenses ecology, ecological restoration principles and a range of eco-revetment models in riparian zone restoration for Xianghe Segment of China's Grand Canal (XSCGC). Based on field trip investigation, the restoration considerations involve the current status quo of the segment's riparian zone. In addition to the analysis of key flood control areas, the restoration considers the main functions of various landscape components. The riparian zone is divided into five typical sections: the wetland ecological conservation section in the upper reaches, the wetland ecological conservation section in the lower reaches, the riverside leisure and entertainment section in the middle reaches, the restoration and reconstruction section in the middle reaches, and the ecological agricultural section in the lower reaches. Based on the spatial form, human senses and the flood control function of the riparian zone, three typical revetment models are applied, namely original natural revetment, natural revetment, and hybrid revetment. A vegetation plan was proposed for every functional section. The aim of the present study is to provide a reference for the restoration and ecological management of the riparian zone in XSCGC.